Lung Monitoring System Using AI - Mrs. R. Savitha,; Mucheli Lahari,; R.SasiKumar,; S.Sri Sukitha Reddy,; R.K.ShivaaniSree, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The "Lung Monitoring System Using AI" project focuses on continuous health monitoring for individuals with respiratory conditions using advanced sensors and AI technologies. Integrated with an Arduino development board, the system uses various sensors, including gas and temperature sensors, to collect real-time data on lung health. The collected data is processed by machine learning algorithms to detect early signs of respiratory issues, allowing for proactive medical intervention. This system aims to enhance patient care by offering continuous, non-invasive monitoring, reducing hospital visits, and providing timely alerts. The study demonstrates the potential of AI and sensor integration in improving lung health management.
Keywords: Lung Monitoring; AI; Machine Learning; Arduino; Respiratory Health; Sensors; Continuous Monitoring; Healthcare; Smart Systems; Early Diagnosis